From broadband horizontal to effective in-plane irradiation: A review of modelling and derived uncertainty for PV yield prediction. (October 2017) - Moretón, R.; Lorenzo, E.; Pinto, A.; Muñoz, J.; Narvarte, L.
Abstract: This article presents an analysis on irradiance modelling and its impact on energy estimation uncertainty. In particular, the calculation of the effective in-plane irradiance from broadband horizontal irradiance is assessed. Thirty-one models for irradiance distribution, decomposition, transposition and spectral correction have been considered. The simulation results have been compared with experimental records obtained during up to three years in 19 locations of the Mediterranean belt with static and tracking systems. Models performance has been evaluated in terms of hourly to yearly weighted errors and frequency distribution similarity. Finally, some best-performing model combinations have been selected.